Neuroleptic malignant syndrome and hypothyroidism. Issue 6 (June 1990) - Moore, A P; Macfarlane, I A; Blumhardt, L D
Abstract : Two patients with primary hypothyroidism who developed neuroleptic malignant syndrome (NMS) are described. Thyroid disease might predispose to NMS by altering brain dopamine metabolism.